THE RELATIONSHIP BETWEEN PARENTING PATTERN OF PARENTS TOWARDS TEMPER TANTRUM IN PRE-SCHOOL CHILDREN IN AN INTEGRATED EARLY CHILDHOOD EDUCATION INSAN MADANI MEUKEK - zakiyah, zakiyah; Nasution, Nurromsyah (International Journal on ObGyn and Health Sciences, 2024)
Temper tantrums are emotional outbursts such as screaming while rolling on the floor, kicking, banging your head against the floor or wall, hitting yourself or others, crying, cursing. The impact of temper tantrums on children can pose a risk of injury, if they occur in the environment of friends of the same age it can affect the development of children of their age, because the characteristics of children imitate what they observe. Parenting style is a factor in the occurrence of temper tantrums. The purpose of this study was to determine parenting styles for temper tantrums in pre-school children. The design of this research is descriptive analytic with cross sectional study approach. This research was conducted at the Insan Madani Meukek Integrated Preschool in December 2022. The population in this study totaled 76 respondents. The sampling technique used the total sampling technique. The parenting research instrument used the Parental Authority Questionnaire (PAQ) and temper tantrums with 33 questions. The data analysis used was univariate and bivariate analysis. The results of the chi square test showed that parenting style was related to temper tantrums in pre-school children (P<0.000). It is hoped that parents can apply good parenting, such as democratic parenting where this parenting style is considered good for children because the risk of temper tantrums in children is lower than authoritarian and permissive parenting.